Determinan Loyalitas Nasabah Bank NTB Syariah - Selamat Muliadi (LPPM ISNJ Bengkalis, 2022)
This research aims to analyze the factors influencing customer loyalty at Bank NTB Syariah. These factors include service performance, customer relationship marketing, and marketing mix. This research applies quantitative techniques and is analyzed using multiple linear regressions. The research population is all customers of Bank NTB Syariah Pancor branch offices, totalling 47,853. Sampling applied the non-probability method of the accidental sampling type, with Slovin measurements obtained from 100 samples. The research results show that partially service performance, customer relationship marketing, and marketing mix have a positive and significant effect on customer loyalty. Simultaneously these three factors have a significant effect on customer loyalty. Research results can be a reference for further research examining similar issues. Then it can become a reference material for Bank NTB Syariah to improve the strategy of the three factors in gaining customer loyalty.